IL‐12Rβ2 is critical for survival of primary Francisella tularensis LVS infection. Issue 5 (1st May 2013) - Melillo, Amanda A.; Foreman, Oded; Elkins, Karen L.
Abstract : IL‐12Rβ2 is critical in parenteral and mucosal host resistance to primary Francisella tularensis LVS infection, and controls liver damage. Abstract : Using a panel of vaccines that provided different degrees of protection, we previously identified the IL‐12 receptor subunit β2 as a mediator, whose relative expression correlated with strength of protection against secondary lethal challenge of vaccinated mice with an intracellular bacterium, the LVS of Francisella tularensis . The present study therefore tested the hypothesis that IL‐12Rβ2 is an important mediator in resistance to LVS by directly examining its role during infections. IL‐12Rβ2 KO mice were highly susceptible to LVS primary infection, administered i.d. or i.n. The LD50 of LVS infection of KO mice were 2 logs lower than those of WT mice, regardless of route. Five days after infection with LVS, bacterial organ burdens were significantly higher in IL‐12Rβ2 KO mice. IL‐12Rβ2 KO mice infected with lethal doses of LVS had more severe liver pathology, including significant increases in the liver enzymes ALT and AST. Despite decreased levels of IFN‐γ, LVS‐vaccinated IL‐12Rβ2 KO mice survived large lethal LVS secondary challenge. Consistent with in vivo protection, in vitro intramacrophage LVS growth was well‐controlled in cocultures containing WT or IL‐12Rβ2 KO LVS‐immune splenocytes. Thus, survival of secondary LVS challenge was not strictly dependent on IL‐12Rβ2. However, IL‐12Rβ2 is important in parenteral and mucosal host resistance to primary LVS infection and in the ability of WT mice to clear LVS infection and serves to restrict liver damage.